“You’re a teacher you’re a mother, you’re a worker”: Gender inequality during COVID‐19 in Ireland - Clark, Serena; McGrane, Amy; Boyle, Neasa; Joksimovic, Natasha; Burke, Lydia; Rock, Nicole; Katriona O’ Sullivan (Gender, Work and Organization, 2021)
The novel coronavirus (COVID‐19) was declared a global pandemic in March 2020. Unlike previous highly contagious diseases that brought the threat of global instability this century such as SARS‐CoV, Zika virus (ZIKV), Swine flu (H1N1), and the Avian flu (H5N1), COVID‐19 was unable to be contained. Global restrictions were implemented to curb the spread of the virus, which included but were not limited to the closure of all educational institutions and the advice to engage in remote working. This study aims to understand the experience of working mothers who managed work and home duties during the COVID‐19 pandemic in Ireland. Thirty working mothers were interviewed in this study, and qualitative analyses were conducted to gain insight into their work and family life during the restrictions. The findings of the analysis indicate that working mothers have been negatively impacted by COVID‐19 in relation to their psychological well‐being, experiences of negative emotions, and the redefinition of family dynamics, in which working mothers have adopted additional and disproportionate care burden. These findings are consistent with the current research arguing that COVID‐19 has highlighted an increase in the gender gap in domestic labor as well as the undermining of career advancement for working mothers.
Keywords: approches et analyses; charge mentale; conciliation famille-travail; division sexuelle du travail; europe; famille; irelande; projet charge mentale; rapports sociaux de sexe; régions géographiques; santé; soins aux enfants; thématiques; travail; travail domestique

Hidden in plain sight: Gender analysis of the environmental and social impact assessment of the East African crude oil pipeline - Hill, Christina; Namara, Charité; Orcaya, Jane; Bogrand, André; Sellwood, Scott A. (Impact Assessment and Project Appraisal, 2021)
Large-scale mining, oil, and gas projects can have a profound and negative affect on women’s rights and gender equality. Adverse impacts include the disruption of family and social life; the increased risks to health and safety, especially in terms of domestic and sexual violence; environmental degradation; as well as changing access to and control over land and livelihoods. These adverse impacts fall most heavily on women. This case study focused on the East African Crude Oil Pipeline (EACOP). It shows that conventional environmental and social impact assessment (ESIA) processes may not identify all potential adverse impacts on women, and can fail to analyse the implications of potential impacts on gender norms and gender power relations, leading to a downplaying of the significance of these impacts. The implications for women and girls’ health and safety resulting from the in-migration of large numbers of mostly men seeking project employment and other opportunities and increases in women’s unpaid care work are two potential adverse impacts the EACOP ESIA failed to identify. Strengthening gender analysis within the current suite of impact assessment tools and methodologies, particularly for extractive industries projects, is therefore urgently needed. © 2021 IAIA.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; environnement; extractivisme; industrie pétrolière; ouganda; patriarcat; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; santé des femmes*; systèmes d'oppressions; thématiques; violences

La charge mentale écologique : un poids supplémentaire pour les femmes - Mathieu, Salomé (Milk Magazine, 2021)
Après la charge mentale domestique, la charge mentale écologique semble elle aussi aliéner tout particulièrement les femmes. Zoom sur ce concept inhérent aux combats écolo d’aujourd’hui, ce qu’il recoupe, et comment, peut-être, réussir à s’en affranchir.
Keywords: 2000 à aujourd'hui; approches et analyses; charge mentale; environnement; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; systèmes d'oppressions; thématiques; travail; travail invisible